Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.2298/mpns1402038p
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris and laser therapy: Crucial role of dentists

Abstract: Even though available literature suggests that low-level laser therapy can be efficiently used in treatment of oral pemphigus vulgaris, either independently or as a part of combined therapy approach, these results should be interpreted with caution since there are no solid evidence-based proofs to provide the guidelines for the treatment of pemphigus vulgaris with low-level laser therapy. Therefore, further long-term randomized controlled clinical studies are necessary in order to give any solid recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Several studies have reported the benefits of LLLT in oral mucositis and suggested that the combination of infrared and red lasers enhances tissue repair and reduces pain, the need for painkillers, and additional hospital costs 15,16 . Although there are few studies using LLLT as a treatment for PV, some have already reported improvement in the healing of oral lesions and the analgesic effect, so it can be used in addition to drug treatments 9,17,18 . Therefore, we reinforce that LLLT may be used as an adjunct to systemic treatment.…”
Section: Discussionsupporting
confidence: 53%
“…Several studies have reported the benefits of LLLT in oral mucositis and suggested that the combination of infrared and red lasers enhances tissue repair and reduces pain, the need for painkillers, and additional hospital costs 15,16 . Although there are few studies using LLLT as a treatment for PV, some have already reported improvement in the healing of oral lesions and the analgesic effect, so it can be used in addition to drug treatments 9,17,18 . Therefore, we reinforce that LLLT may be used as an adjunct to systemic treatment.…”
Section: Discussionsupporting
confidence: 53%
“…LLLT has been introduced as a new treatment option for patients with PV lesions unresponsive to conventional therapy. Pavlic et al 23 in a review article evaluating the available literature on the effects of LLLT in the treatment of pemphigus concluded that LLLT is efficient in the treatment of recalcitrant oral pemphigus lesions, either used alone 3,24 or as an adjunct to conventional treatment modalities. 7 The present study aimed at evaluating the effects of LLLT in the treatment of recalcitrant pemphigus lesions.…”
Section: Discussionmentioning
confidence: 99%